EXPLORING PERSONAL INNOVATIVENESS AS A DRIVING FACTOR IN THE TECHNOLOGY ACCEPTANCE MODEL FOR MYTELKOMSEL IMPROVING - Dira Yulianti; Siska Noviaristanti (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the role of Personal Innovativeness in influencing the actual use of the MyTelkomsel application through an extended Technology Acceptance Model (TAM). In this model, Personal Innovativeness is positioned as a core construct that influences three key user perceptions: Perceived Ease of Use, Perceived Usefulness, and Perceived Enjoyment. A total of 355 respondents participated in the study, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that seven out of eight hypothesized paths between constructs in the model demonstrate statistically significant effects. The only non-significant relationship is found between Perceived Ease of Use and Attitude Toward Use, suggesting that ease of use is no longer a major determinant of user attitudes toward digital applications, possibly because it is now perceived as a basic standard in technology usage. Conversely, Personal Innovativeness consistently exerts a significant influence on all three key perceptions, which in turn affect users’ attitudes, intentions, and actual behaviors. These results underscore the strategic role of innovative personal characteristics in driving adoption and active engagement with digital applications. The practical implications highlight the importance of user segmentation based on innovation levels, the development of enjoyable features, and the refinement of user experience to promote sustained engagement within digital ecosystems such as MyTelkomsel.